Perancangan Aplikasi Kasir Berbasis Web pada UMKM Menggunakan Metode Agile (Studi Kasus: Chilor Surya) - Andri Ramdani; Ika Setiawan (PT. Hasba Edukasi Mandiri, 2026)
The problem faced by Chilor Surya MSME is that sales transactions are still recorded manually, which increases the risk of calculation errors, data loss, delays in report preparation, and difficulties for the owner in monitoring income in real time. In addition, the absence of a system that regulates different access rights between the owner and cashier results in less controlled sales data management and potential inconsistencies in information. These conditions indicate the need for a computerized system that can support transaction processes and generate reports more effectively and accurately. This study aims to design and develop a web-based cashier application for Chilor Surya using the Agile method, which was chosen for its ability to adapt to user needs gradually through iterative development. The system provides login features with role-based access control, product and category data management, sales transactions, payment methods including cash and QRIS, and sales report generation that can be printed in PDF format and exported to Excel. System testing was conducted using the blackbox testing method, and the results show that all features function according to user requirements. The developed application improves the effectiveness of transaction recording, minimizes errors, and helps the owner monitor and control sales activities more quickly, accurately, and efficiently.